A MicroRNA302-367-Erk1/2-Klf2-S1pr1 Pathway Prevents Tumor Growth via Restricting Angiogenesis and Improving Vascular Stability. Issue 1 (6th January 2017) - Pi, Jingjiang; Tao, Ting; Zhuang, Tao; Sun, Huimin; Chen, Xiaoli; Liu, Jie; Cheng, Yu; Yu, Zuoren; Zhu, Helen He; Gao, Wei-Qiang; Suo, Yuanzhen; Wei, Xunbin; et al.
Abstract : Rationale: : Angiogenic hypersprouting and leaky vessels are essential for tumor growth. MicroRNAs have unique therapeutic advantages by targeting multiple pathways of tumor-associated angiogenesis, but the function of individual miRNAs of miR302-367 cluster in angiogenesis and tumors has not yet been fully evaluated. Objective: : To investigate the functions of miR302-367 in developmental angiogenesis and tumor angiogenesis and explore the molecular mechanisms of microRNA for the treatment of pathological neovascularization-related diseases. Methods and Results: : Here, we show that miR302-367 elevation in endothelial cells reduces retinal sprouting angiogenesis and promotes vascular stability in vivo, ex vivo, and in vitro. Erk1/2 is identified as direct target of miR302-367, and downregulation of Erk1/2 on miR302-367 elevation in endothelial cells increases the expression of Klf2 and in turn S1pr1 and its downstream target VE-cadherin, suppressing angiogenesis and improving vascular stability. Conversely, both pharmacological blockade and genetic deletion of S1pr1 in endothelial cells reverse the antiangiogenic and vascular stabilizing effect of miR302-367 in mice. Tumor angiogenesis shares features of developmental angiogenesis, and endothelial specific elevation of miR302-367 reduces tumor growth by restricting sprout angiogenesis and decreasing vascular permeability via the same Erk1/2-Klf2-S1pr1 pathways. Conclusions: : MiR302-367 regulation of an Erk1/2-Klf2-S1pr1 pathway in the endothelium advances our understanding of angiogenesis, meanwhile also provides opportunities for therapeutic intervention of tumor growth. Abstract : Supplemental Digital Content is available in the text.